Minimizing Paravalvular Regurgitation With the Novel SAPIEN 3 Ultra TAVR Prosthesis: A Real-World Comparison Study - Tamm, Alexander R.; Hell, Michaela M.; Geyer, Martin; Kreidel, Felix; da Rocha e Silva, Jaqueline G.; Seidl, Meike; Ruf, Tobias F.; Kornberger, Angela; Beiras-Fernandez, Andres; Münzel, Thomas; von Bardeleben, Ralph Stephan (Frontiers in Cardiovascular Medicine, 2021)
Objectives We investigated performance and outcome of the latest-generation balloon-expandable SAPIEN 3 Ultra prosthesis (S3U) compared to the established SAPIEN 3 prosthesis (S3) in a real-world cohort, with focus on paravalvular regurgitation (PVR). Background PVR is an adverse prognostic indicator of short- and long-term survival after transcatheter aortic valve replacement (TAVR). The S3U has been designed to improve sealing. Methods We enrolled 343 consecutive patients presenting with severe native aortic valve stenosis eligible for a balloon-expandable prosthesis. The established S3 was implanted in the first 200 patients, the following 143 patients received the novel S3U after introduction in our institution. Primary endpoint was PVR after TAVR. Furthermore, we investigated procedural parameters and in-hospital and 30-day outcome. Results PVR was significantly lower in the S3U cohort compared to the S3 cohort. They differed in their rate of mild PVR (11.2 vs. 48.0%, p<0.001), whereas at least moderate PVR was similarly low in both cohorts (0.7 vs. 0.5%, p=0.811). A significant reduction of post-dilatation rate, fluoroscopy time and amount of contrast was observed in patients treated with the novel S3U (p<0.001). The rate of adverse events in the in-hospital course and at 30-days were similarly low. At 30 days more patients receiving S3U improved in NYHA class (improvement ≥2 grades 34.6% vs. 19.9% , p=0.003). Conclusion The current study provides evidence that the novel S3U strongly minimizes PVR, thereby demonstrating the efficacy of improved sealing. Further studies will have to address if the observed reduction of PVR with S3U has prognostic significance.